Jose Luis Carbajal Briceño. Impact of the market economy on the Piro production and kinship systems. Thesis presented to the Pontifical Catholic University for the degree of Bachelor in Anthropology - Carbajal Briceño, José Luis (1996)
This review does not present a summary.